AN ERROR ANALYSIS OF ENGLISH SIMPLE PRESENT TENSE OF THE SECOND YEAR STUDENTS OF SMP N 1 SUSUKAN REGENCY OF SEMARANG IN THE ACADEMIC YEAR 2003/2004 - Agus Safudin (Register Journal, 2009)
The aim of this research is to find out how far the errors of simple present tense produced bythe second year students of SMP N 1 Susukan. The research was conducted at State Junior High School (SMP N) 1 Susukan, Regency of Semarang, Central Java, Indonesia. The objects of this research were the eighth graders. This is quantitative research. The writer uses random sampling by lottery. There are about 75 students and the writer took 50% as the sample.The errors made by the students were divided into eight aspects. (1) Error in using auxiliary is 36.75%. (2) Error in using plural noun is 22.90%. (3) Error in using to be is (am, is, are,) is 7.69%.(4) Error in adverb of manneris 4.27%. (5) Error in using verb in simple present tense is 4.78%. (6) Error in using possessive sentence 5.24%. (7) Error in using imperative sentence is 0.34%. (8) Error due to ignorant is 11.28%. Relating to those errors there should be the preventing efforts by the teachers such as providing lots of examples of English and Indonesian sentences so that the students have greater understanding about the difference of those languages.Keywords: Error Analysis; Simple Present Tense; SMP N 1 Susukan